2019
DOI: 10.1007/978-3-030-20954-4_17
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Portuguese University Teachers About Critical Thinking Educational Practices

Abstract: Promoting students' Critical Thinking (CT) in Higher Education Institutions (HEI) has been an essential and challenging goal in the 21 st century. This exploratory research study attempted to characterize how CT is being fostered in Portuguese HEI. Semi-structured interviews were carried-out with 5 university teachers from different domains, focusing several topics: CT notion, CT aims, CT approach, interventions, teaching strategies, learning materials, assessment methods, challenges and barriers. Results high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
1
1
0
1
Order By: Relevance
“…They reported a lack of opportunities to ask questions, participate in discussions or express their opinion. Similar results were obtained in a Portuguese study (Morais et al, 2019) in which university teachers expressed their willingness to promote CT within their own courses. However, the findings revealed that the teachers did not possess a complete understanding of the CT concept, though they did strive to teach it using a variety of activities and learning materials.…”
Section: Fostering Critical Thinking In a School Settingsupporting
confidence: 85%
“…They reported a lack of opportunities to ask questions, participate in discussions or express their opinion. Similar results were obtained in a Portuguese study (Morais et al, 2019) in which university teachers expressed their willingness to promote CT within their own courses. However, the findings revealed that the teachers did not possess a complete understanding of the CT concept, though they did strive to teach it using a variety of activities and learning materials.…”
Section: Fostering Critical Thinking In a School Settingsupporting
confidence: 85%
“…A nivel internacional, existe un creciente interés por parte de profesores e instituciones de educación superior en evaluar el PC de los estudiantes universitarios . Sin embargo, se han señalado repetidamente las limitaciones de estos estudios, como la falta de claridad y rigor en la conceptualización del constructo, los principios de diseño, los criterios que sustentan la enseñanza y evaluación del PC, los informes estadísticos, la presentación de los datos y la discusión de los resultados (Cruz et al, 2017;Morais et al, 2019;Puig et al, 2019).…”
Section: Introductionunclassified
“…Besides, it is possible that the teachers in my studies may have been more positive about CT compared to the average (inter)national higher education teacher, because they all worked at university of applied sciences that pays a lot of attention to the topic of CT. Yet, other international studies have also found that teachers perceive teaching CT as highly relevant (though they differ in views on what CT is and how to teach it; Choy & Cheah, 2009;Dumitru, 2018;Morais et al, 2018;Paul et al, 1997;Stedman & Adams, 2012). These results are still hard to compare directly as all studies relied on very different research methods and on small samples mostly.…”
Section: Discussion: Implications and Future Directionsmentioning
confidence: 99%